Analisis Pendapatan Petani Pengguna Benih Padi Bersertifikat dan Tidak Bersertifikat di Kabupaten Bantul - Anisya, Ayu Putri Merry; Wibowo, Teguh Nova Eko (LP3M Universitas Putra Bangsa, 2024)
Rice, as a commodity that plays a central role in Indonesian society, not only serves as the primary source of food but also the rice farming sector is a source of livelihood for farmers and the community. One way to increase rice production is by using certified rice varieties and types. Seeds play an important role in agriculture, and one form of technology application to increase seed productivity is through the use of superior varieties with official licenses or certifications. In addition, uncertified seeds have weaknesses such as low resistance to pests and diseases, non-uniform growth, and a decline in quality if planted repeatedly over a long period. The difference in the use of certified and uncertified seeds can affect farmer productivity and income. Thus, this study aims to analyze the difference in productivity between farmers who use certified and uncertified rice seeds in Bantul Regency. The location determination technique was carried out using the Purposive Sampling Method, while sample taking in this study was carried out using simple random sampling, which is random data taking from a portion of the entire population. The number of samples of craftsmen taken was 50 farmers. The results of the analysis show that the income obtained by farmers can be seen that the income obtained by farmers who use certified seeds is higher than that of farmers who use uncertified seeds. This can be seen that the production produced by farmers who use certified seeds is greater than that of farmers who use uncertified seeds. It can be seen that the income obtained by farmers who use certified seeds is Rp 7,017,358 in the rainy season and Rp 7,378,604 in the dry season, while the income of farmers who use uncertified seeds is Rp 6,604,672 in the rainy season and Rp 6,248,007 in the dry season. This income is influenced by certified seeds and the costs incurred by farmers each season, as well as the production produced, and the costs incurred and production produced each season vary, so the income obtained by farmers also varies.